Leaf Disease Detection using Digital Image Processing with SVM Classifier - Gaikwad, Sagar; Shinde, Sagar (International Journal of Computer Sciences and Engineering, 2019)
Recognizable proof of the mango leaf malady is the primary objective to avert the misfortunes and nature of horticultural item. In India mango natural product harvest is broadly developed. So infection discovery and grouping of mango leaf is basic for maintainable farming. It`s impractical to rancher, to screen consistently the mango illness physically. It requires the over the top handling time, colossal measure of work, and some aptitude in the mango leaf ailments. To recognize and characterize the mango ailment we need quick programmed procedure so we use SVM classifier strategy. This paper shows predominantly five phases, viz picture securing, pre-handling, division, include extraction and SVM order. This paper is proposed to profit in the location and order of mango leaf infection utilizing bolster vector machine (SVM) classifier.